Protective Effects of a New C-Jun N-terminal Kinase Inhibitor in the Model of Global Cerebral Ischemia in Rats - Plotnikov, Mark B. (Molecules, 2019)
c-Jun N-terminal kinase (JNK) is activated by various brain insults and is implicated in neuronal injury triggered by reperfusion-induced oxidative stress. Some JNK inhibitors demonstrated neuroprotective potential in various models, including cerebral ischemia/reperfusion injury. The objective of the present work was to study the neuroprotective activity of a new specific JNK inhibitor, IQ-1S (11H-indeno[1,2-b]quinoxalin-11-one oxime sodium salt), in the model of global cerebral ischemia (GCI) in rats compared with citicoline (cytidine-5′-diphosphocholine), a drug approved for the treatment of acute ischemic stroke and to search for pleiotropic mechanisms of neuroprotective effects of IQ-1S. The experiments were performed in a rat model of ischemic stroke with three-vessel occlusion (model of 3VO) affecting the brachiocephalic artery, the left subclavian artery, and the left common carotid artery. After 7-min episode of GCI in rats, 25% of animals died, whereas survived animals had severe neurological deficit at days 1, 3, and 5 after GCI. At day 5 after GCI, we observing massive loss of pyramidal neurons in the hippocampal CA1 area, increase in lipid peroxidation products in the brain tissue, and decrease in local cerebral blood flow (LCBF) in the parietal cortex. Moreover, blood hyperviscosity syndrome and endothelial dysfunction were found after GCI. Administration of IQ-1S (intragastrically at a dose 50 mg/kg daily for 5 days) was associated with neuroprotective effect comparable with the effect of citicoline (intraperitoneal at a dose of 500 mg/kg, daily for 5 days).The neuroprotective effect was accompanied by a decrease in the number of animals with severe neurological deficit, an increase in the number of animals with moderate degree of neurological deficit compared with control GCI group, and an increase in the number of unaltered neurons in the hippocampal CA1 area along with a significant decrease in the number of neurons with irreversible morphological damage. In rats with IQ-1S administration, the LCBF was significantly higher (by 60%) compared with that in the GCI control. Treatment with IQ-1S also decreases blood viscosity and endothelial dysfunction. A concentration-dependent decrease (IC(50) = 0.8 ± 0.3 μM) of tone in isolated carotid arterial rings constricted with phenylephrine was observed after IQ-1S application in vitro. We also found that IQ-1S decreased the intensity of the lipid peroxidation in the brain tissue in rats with GCI. 2.2-Diphenyl-1-picrylhydrazyl scavenging for IQ-1S in acetonitrile and acetone exceeded the corresponding values for ionol, a known antioxidant. Overall, these results suggest that the neuroprotective properties of IQ-1S may be mediated by improvement of cerebral microcirculation due to the enhanced vasorelaxation, beneficial effects on blood viscosity, attenuation of the endothelial dysfunction, and antioxidant/antiradical IQ-1S activity.